PyPWDFT: A Lightweight Python Software for Single-Node 10K Atom Plane-Wave Density Functional Theory Calculations - Gao, Jun; Fu, Lizhong; Jiao, Shizhe; Zhang, Zhenlin; Chen, Sheng; Zhang, Zhiyuan; Wu, Wentiao; Wan, Lingyun; Li, Jielan; Hu, Wei; Yang, Jinlong (Journal of chemical theory and computation, 2025)
PyPWDFT is a Python software designed for performing plane-wave density functional theory (DFT) calculations. It can perform large-scale DFT calculations using only a single process on a single node, including local density functional for 10,000 atoms and nonlocal hybrid functional for 4096 atoms. Our benchmark test results demonstrate that PyPWDFT achieves performance comparable to that of Fortran/C++ codes, despite being developed in a native Python environment. In addition, it requires only NumPy, SciPy, and CuPy, enabling CPU-GPU heterogeneous computing, achieving a two-order-of-magnitude speedup compared to single-threaded CPU execution. Due to its excellent cross-platform compatibility, medium-scale DFT calculations can be performed through a graphical user interface on personal computers and Windows systems using consumer-grade GPUs, such as the NVIDIA GeForce RTX 4090. The computational efficiency is comparable to that of professional-grade GPUs such as the NVIDIA V100. The efficient performance, scalability to handle large-scale systems, high numerical accuracy, and different interfaces for molecular dynamics collectively underscore the considerable potential of PyPWDFT to develop into versatile DFT software.